A comparative study of the pharyngeal plate of Apoidea (Hymenoptera: Aculeata), with implications for the understanding of phylogenetic relationships of bees. (May 2019) - Porto, Diego S.; Almeida, Eduardo A.B.
Abstract: The pharyngeal plate is a morphological complex with extensive anatomical variation among bees and, therefore, potential as a source of phylogenetic information. The pharyngeal plate of bees is divided into four morphologically distinct regions: sitophore, hypopharyngeal lobe, pharyngeal rods, and median oral plate. In this work we illustrate and document in detail for the first time the pharyngeal plate of 43 bee species, providing descriptions of the morphological variation and contrasting these findings with representatives of apoid wasps (Crabronidae and Sphecidae). We evaluate and discuss the potential of this structure as a rich source of morphological information in the context of bee phylogeny and any research potentially impacted by comparative morphological data. The shape of the hypopharyngeal lobe is highly variable among suprageneric taxa of bees and can be readily employed to characterise taxa at various levels. We argue that the global patterns in the variation of the pharyngeal plate can provide information for phylogenetic inference within bees and constructed and coded 10 characters that encompass the most noticeable morphological differences discussed herein. Graphical abstract: Image 1 Highlights: The pharyngeal plate includes four elements: sitophore, hypopharyngeal lobe, pharyngeal rods, and median oral plate. General patterns of morphological variation of the pharyngeal plate provide information for phylogenetic inference in bees. The hypopharyngeal lobe is highly variable and can characterise small groups of bee species or genera.